2017
DOI: 10.1128/cmr.00113-16
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Fungal Endophthalmitis

Abstract: Endophthalmitis is a severe eye infection that may result in permanent loss of useful vision in the affected eye. Most cases are exogenous and occur as a complication of cataract surgery, an intravitreal injection, or penetrating ocular trauma. Endogenous endophthalmitis results from hematogenous seeding of the eye by bacteria or fungi, but bacteremia or fungemia may be transient and patients may present without symptoms of systemic infection. Nearly all endophthalmitis patients present with decreased vision, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
495
2
35

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(548 citation statements)
references
References 83 publications
16
495
2
35
Order By: Relevance
“…Notwithstanding the procedure of identification and contrary to earlier reports of C. albicans being the most common yeast in eye infections 28,29 this study confirms that C. parapsilosis is more commonly associated with eye infections compared with all other species. Most studies reporting yeast eye infections have found C. parapsilosis a close second to C. albicans.…”
Section: Discussioncontrasting
confidence: 56%
“…Notwithstanding the procedure of identification and contrary to earlier reports of C. albicans being the most common yeast in eye infections 28,29 this study confirms that C. parapsilosis is more commonly associated with eye infections compared with all other species. Most studies reporting yeast eye infections have found C. parapsilosis a close second to C. albicans.…”
Section: Discussioncontrasting
confidence: 56%
“…Most cases of endophthalmitis are exogenous and are due to direct inoculation of organisms into the globe from trauma or ocular surgery or are an extension of corneal infection that seeds the aqueous humor before spreading into the vitreous humor (13). Less commonly, endogenous endophthalmitis ( Fig 5) is due to organisms that seed the highly vascular choroid first before extending into the vitreous humor.…”
Section: Endophthalmitismentioning
confidence: 98%
“…Clinical features include eye pain, decreased vision, and red eye. 99,100 Progression may be rapid. For example, certain pathogens such as Bacillus cereus may result in complete vision loss in the affected eye within 24 to 48 hours.…”
Section: Retinoblastomamentioning
confidence: 97%